1971
DOI: 10.1007/bf02531319
|View full text |Cite
|
Sign up to set email alerts
|

Composition of wax esters, triglycerides and diacyl glyceryl ethers in the jaw and blubber fats of the Amazon River dolphin (Inia geoffrensis)

Abstract: The lower jaw fat of the Amazon River dolphinInia geoffrensis contains 52.8% wax ester, 44.7% triglyceride and 2.5% diacyl glyceryl ether, while its dorsal blubber fat is >98% triglyceride. Examination of the intact lipids, the derived fatty acids and the derived fatty alcohols by gas chromatography reveals that the blubber triglycerides show characteristics of freshwater fish fats, but the jaw fat lipids have several distinctive features. Jaw fat wax esters, triglycerides and diacyl glyceryl ethers are all ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 41 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Gill and Tucker (1930) confirmed the structure as isovaleric acid in Tursiops, and Lovern (1934) noticed that levels of i-5:0 varied tremendously between tissues, with high levels in the acoustic fats, detectable levels in the blubber, and none in the heart, lungs and liver of Phocoena. A flurry of activity in the 1970s (see Ackman et al, 1971Ackman et al, , 1973Ackman et al, , 1975Litchfield et al, 1975Litchfield et al, , 1976Varanasi et al, 1975) led to the characterization of acoustic lipids in a wider range of species, and the phylogenetic patterns of unusual lipids recognized today.…”
Section: Lipids In the Acoustic Fatsmentioning
confidence: 99%
“…Gill and Tucker (1930) confirmed the structure as isovaleric acid in Tursiops, and Lovern (1934) noticed that levels of i-5:0 varied tremendously between tissues, with high levels in the acoustic fats, detectable levels in the blubber, and none in the heart, lungs and liver of Phocoena. A flurry of activity in the 1970s (see Ackman et al, 1971Ackman et al, , 1973Ackman et al, , 1975Litchfield et al, 1975Litchfield et al, , 1976Varanasi et al, 1975) led to the characterization of acoustic lipids in a wider range of species, and the phylogenetic patterns of unusual lipids recognized today.…”
Section: Lipids In the Acoustic Fatsmentioning
confidence: 99%
“…In odontocetes, the melon and the large fat bodies found in and around the mandibular region serve as part of the acoustic pathway and are known as the acoustical window for sound transmission (Norris et al 1961, Norris 1968, Norris and Harvey 1974. The biochemical composition of these "acoustic fats bodies" is different to that of body blubber (Varanasi and Malins 1970, Ackman et al 1971, Litchfield et al 1975, Koopman et al 2006. Acoustic fat bodies contain a high quantity of lipids with high concentrations of unusual endogenous lipids, and their biochemical composition does not seem to be influenced by diet.…”
Section: Blubber Stratificationmentioning
confidence: 99%
“…Biochemically, the blubber structure is based on the lipid content, and the composition and distribution of fatty acids have been widely studied in cetacean species. Studies in balaenopterids and balaenids (Ackman et al 1975, Aguilar and Borrell 1990, Moller et al 2003, Olsen and Grahl-Nielsen 2003, Budget et al 2008 and to a lesser degree in odontocetes (Ackman 1971, Evans et al 2003, Samuel and Worthy 2004, Smith and Worthy 2006, Koopman 2007, Bagge et al 2012, have demonstrated that the lipid content and quantity and quality of fatty acids vary among blubber layers, indicating blubber stratification. Blubber was found to be histologically stratified in different layers in the harbour porpoise, Phocoena phocoena, and the bottlenose dolphin, Tursiops truncatus (Struntz et al 2004, Montie et al 2008, based on the size, shape, and metabolic characteristics of the adipocytes as well as on the abundance of collagen fibres.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, there are higher levels of long chain fatty acids in blubber compared to the ear fat. Odontocete acoustic fats, including the melon and peri-mandibular fats, are known to contain fatty acids and alcohols with a lower average chain length than in the blubber of the same animal (Ackman et al, 1971;Litchfield et al, 1976). This contributes to the reduced sound speeds found in acoustic fats because sound speeds through shorter fatty acids are slower than through longer fatty acids (Guow and Vlugter, 1967;.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…For example, sperm whale and beaked whale (kogiids, physterids, and ziphiids) blubber is made up of primarily wax esters, whereas the melon and jaw fats contain high levels ( >50%) of triacylglycerols Litchfield et al, 1976;Koopman et al, 2006;Koopman, 2007). Studies comparing the lipids of blubber and acoustic fats of odontocetes have shown that the fatty acids found in the acoustic fats contain higher levels of endogenous lipids and consistently have lower average chain lengths than those found in the blubber (Ackman et al, 1971;Litchfield et al, 1976;Koopman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%